Analisis Industri Rotan Jawa Barat dengan Model Constant Elasticity of Substitution (CES) dan Model Cobb-Douglas - Danilwan, Yuris (Jurnal Trikonomika, 2010)
Rattan industry in West Java is one of a growing industry, an indication can be seen from the resulting increase in real output tends to increase from year to year (1996, 2008). Nevertheless, the increase in aggregate output is not necessarily in line with the level of efficiency, increased scale of business, and improving intensity of production factors. This means that output is not necessarily match what is expected by the stake holders, as well as fringe benefits provided for the use of production factors, not necessarily in accordance with the wishes and desires of capital permilik labor. By using CES production function. The results of this study indicate several things: (1) the elasticity of substitution the use of capital and labor inputs in the rattan industry in West Java is inelastic (2) referring to the criteria of returns to scale, the scale parameter when the results showed a decreasing returns to scale or diminishing returns to scale, (3) coefficient technical efficiency of the rattan industry in West Java is formed into a first differentiation CES production function, and (4) the intensity factor of production in the rattan industry in West Java tends to be capital intensive.